A cross-sectional study on loneliness among orphans - Noradilah Md Nordin,; Fatin Aliana Mohd Radzi,; Munira Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Loneliness is one of the indicators of emotional development in orphans, who often face social isolation due to the absence of parental figures and the difficulties in finding adequate social support. Specific objectives were: (i) identify the level of loneliness among orphans and (ii) identify the gender differences in loneliness among orphans. A total of 242 respondents were recruited in this study, aged 10 to 14 years, from a city on the East Coast of Malaysia. Children’s Loneliness Questionnaire (CLQ) which consisted of 24 items developed by Asher (1984) was used to measure loneliness. Higher scores for the CLQ indicated a higher level of loneliness. Results showed that 72.3% of respondents experienced a moderate level of loneliness followed by 14.9% and 12.8% for low and high respectively. Also, this study found that there was a significant difference between male and female in terms of loneliness (t = 2.66, p < 0.05). Males experienced higher loneliness than females. Early detection of loneliness is helpful in promoting healthier emotional development among orphans.